Effect of entrepreneurial orientation on competency and micro-enterprise performance. Issue 3 (29th November 2018) - Al Mamun, Abdullah; Fazal, Syed Ali
Abstract : Purpose: This study aims to examine the effect of creativity and innovativeness, risk taking propensity, proactiveness and autonomy on entrepreneurial competency and performance among micro-enterprises in Kelantan, Malaysia. Design/methodology/approach: Adopting a cross-sectional design, the authors collected data from 403 micro-entrepreneurs who were registered under "Majlis Amanah Rakyat" and "Majlis Agama Islam dan Adat Istiadat". Quantitative data were collected through structured interviews from September 2017 to December 2017. Findings: The findings revealed that creativity and innovativeness, proactiveness and autonomy had a positive influence on entrepreneurial competencies. In addition, autonomy and entrepreneurial competencies had a positive effect on micro-enterprise performance. Then, entrepreneurial competencies showed a mediating effect on the relationships between creativity, innovativeness, autonomy and micro-enterprise performance. Originality/value: The findings contributed to resource-based view and enriched the entrepreneurship literature, particularly in the context of small businesses in emerging economies. This study recommended underlying organizations to pay attention to the improvement of creativity and innovativeness, proactiveness, autonomy and entrepreneurial competencies among low-income entrepreneurs through useful policies and training programs, which were expected to improve micro-enterprise performance and encourage poor households to perform entrepreneurial activities for better socio-economic conditions.